Structural and Optical Properties of Nickel Sulfoselenide (NiSSe) Thin Film for Photoelectrochemical Applications - Sharir, Shariza; Sahaya Anand, T. Joseph; Mat Yusoff, Nurul Hazliza (Journal of Science and Technology, 2018)
The transition metal, nickel is a favourable material to create combination with chalcogenides elements (S, Se and Te) to become either binary or ternary transition metal chalcogenide such NiSe2, NiSe, NiS2 and Ni3Se. Throughout some observation from the previous research regarding the synthesis of ternary transition metal chalcogenide thin film for photoelectrochemical application, the combination of nickel with two chalcogenide elements; S and Se are rarely found due to the nature of selenium and sulphur. In this work, NiSSe thin film is being synthesis onto indium tin oxide (ITO) glass substrates using electrodeposition technique and the structural and optical properties of the films are studied. The resulted thin films are characterized using X-ray diffraction analysis and scanning electron microscope to determine the crystallographic and morphological properties. Optical are also being analysed for their bandgap values in other to determine the suitability of NiSSe thin film for photoelectrochemical properties. Results proved that nickel sulfoselenide thin films are polycrystalline in nature with a good uniformity. The intersection point for the optical analysis gave the direct bandgap. Well-adherent and dark-coloured thin films are derived from the cathodically electrodeposition by using potential in the reduction region. Experimental results proved NiSSe thin films are capable to be used in photoelectrochemical cell application.